Diagnostic performance of the extended focused assessment with sonography for trauma (EFAST) patients in a tertiary care hospital of Nepal - Samjhana Basnet; Sanu Krishna Shrestha; Alok Pradhan; Roshana Shrestha; Anmol Purna Shrestha; Grishma Sharma; Sahil Bade; Latika Giri (Trauma Surgery & Acute Care Open)
Background Thoracoabdominal trauma presents a diagnostic challenge for the emergency physician. The introduction of bedside ultrasonography (USG) provides a screening tool to detect hemoperitoneum, hemothorax, pneumothorax and pericardial effusion in torso injuries.Aim To evaluate the accuracy of extended focused assessment with sonography for trauma (EFAST) for chest and abdominal injuries performed by first responders in a tertiary care hospital of Nepal.Methods This was a prospective study including all trauma patients who obtained either an Injury Severity Score ≥15 or direct trauma to the trunk in 1 year period in the emergency department (ED) of Dhulikhel Hospital-Kathmandu University Hospital. The results of the EFAST were then compared with contrast-enhanced CT (CECT), radiology ultrasound (USG)/chest X-ray, or intraoperative findings when the EFAST was positive. The negative EFAST cases were observed for a minimum of 4 hours in the ED. Descriptive statistics and sensitivity, specificity, positive predictive value, negative predictive value and accuracy were calculated.Results Out of 267 cases, 261 patients underwent an EFAST examination. The sensitivity and specificity were 94.8% and 99.5%, respectively. The negative predictive value was 98.53% whereas the positive predictive value was 98.21%. The overall accuracy was 99.4%.Conclusion The results of this study suggest that EFAST examination performed by first-line healthcare providers is a useful method for assessment of thoracic and abdominal injuries. EFAST was found to have a high specificity (99.5%) and positive predictive value (98.21%) which indicates that it is an effective technique for detecting intra-abdominal or thoracic injuries. However, the effectiveness of EFAST is limited by its being operator dependent, and thereby human error. For negative EFAST cases, we recommend a monitoring period of at least 4 hours, serial fast scan, or further investigation through other methods such as a CECT.Level of evidence Level I